Assessing Reliability and Energy Security Through PLANS and EA-PSM Software Simulations - Piotr Hadaj; Dominik Strzałka (Energies)
This study presents a comparative analysis of PLANS (v. /2019/12/10) and EA-PSM (v. 19.11.15.0) software for power system simulations, focusing on their applications in enhancing energy security and grid reliability. Utilizing the Newton–Raphson algorithm for power flow calculations, both tools offer robust solutions for network balance, addressing various issues, such as voltage distortions and reactive power injection. The research highlights the critical role of these simulations in integrating renewable energy sources and ensuring efficient, sustainable, and resilient power systems. Additionally, the study underscores the multidimensional aspect of energy security as a cornerstone of national stability and economic prosperity.